1989
DOI: 10.1136/jcp.42.11.1169
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of tropical appendicitis.

Abstract: summARY Over the past 25 years, 2921 appendicectomies were performed at this hospital. All were subjected to routine histopathological examination. In 95% of cases, histopathological examination did not add any further information but in 153 (5%) cases, clinically important pathological findings were detected for the first time. Seventy (2-3%) specimens showed typical evidence of tuberculosis. Parasitic infestation was detected in 75 (2.5%), including enterobiasis (1-4%), amoebiasis (0-5%), ascariasis (0 5%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 17 publications
2
54
0
1
Order By: Relevance
“…Role of parasitic infection as a co-factor in appendicitis is controversial even though today. There are only a few evidence about the relation between acute appendicitis and parasites (17)(18)(19). Onset of pathogenesis of acute appendicitis may be due to either inflammation occurring secondary to existence of parasites and their ova, or obstruction of the lumen by parasite itself (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Role of parasitic infection as a co-factor in appendicitis is controversial even though today. There are only a few evidence about the relation between acute appendicitis and parasites (17)(18)(19). Onset of pathogenesis of acute appendicitis may be due to either inflammation occurring secondary to existence of parasites and their ova, or obstruction of the lumen by parasite itself (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Acute appendicitis may develop as a result of the obstruction of the lumen by an adult parasite, whereas it may also develop due to secondary infection by the egg. The mechanism responsible for this pathology is the lymphoid hyperplasia, which develops due to secondary infection (8)(9)(10). In our case, the reason for acute appendicitis was a secondary infection.…”
Section: Resultsmentioning
confidence: 87%
“…7 In another study, it was observed that, in 5% of cases important pathological findings were found incidentally; thus making routine evaluation unavoidable. 4 In the present study, we took up microscopic evaluation of all appendicectomies those are clinically diagnosed as appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…2 According to Foreign studies, acute appendicitis affects males and females about equally, 3 but male predominance is found in majority of the Indian studies. 4 Deaths from appendicitis are very rare, and usually occur in the elderly, in whom the symptoms are less striking in relation to the severity of the disease and in whom silent perforation of the appendix with peritonitis is more common.…”
Section: Introductionmentioning
confidence: 99%